Artificial Intelligence and Applications in Library and Information Science (LIS): Transforming the Future of Libraries - Singh, Deepak (International Journal of Information Studies, 2025)
Artificial Intelligence (AI) is revolutionising various sectors, and Library and Information Science (LIS) is no exception. By leveraging AI technologies, libraries can enhance their services, streamline operations, and improve user experiences. This paper explores the various applications of AI in LIS, the benefits of integrating AI technologies in libraries, and AI tools currently in use within the field. The adoption of AI in libraries signifies a significant evolution in the way these institutions operate and interact with their communities. Through the integration of AI technologies, libraries enhance multiple facets of their operations, such as information organisation, user services, research support, and accessibility. This technological advancement not only boosts the efficiency of library services but also enables personalised user experiences, ultimately promoting increased community engagement and digital literacy. [1][2] AI applications in libraries include automated cataloguing and recommendation systems, as well as chatbots that offer immediate assistance to patrons. These innovations empower libraries to customise their services according to individual user preferences, greatly improving the overall experience. Furthermore, AI is essential in the digitisation and preservation of delicate materials, making historical documents more accessible and ensuring that cultural heritage is safeguarded for future generations. [3][4] Nevertheless, the incorporation of AI in libraries presents its own set of challenges and controversies. Concerns regarding privacy, algorithmic bias, and ethical implications are vital considerations for library professionals as they navigate the intricacies of AI technology. For example, there are apprehensions about the potential for AI systems to reinforce existing inequalities and widen the digital divide, especially among marginalised communities. [5][6] Consequently, libraries must embrace responsible AI practices that emphasise transparency, inclusivity, and ethical use. Libraries must consequently embrace responsible AI practices that emphasise transparency, inclusivity, and user education to alleviate these risks. [7] As libraries progress in the digital era, their function as knowledge facilitators is becoming ever more significant. By adopting AI, libraries not only improve their services but also strengthen their dedication to ensuring equitable access to information, thereby establishing themselves as essential resources in nurturing informed and engaged communities. [8][9].